1993
DOI: 10.1093/carcin/14.4.593
|View full text |Cite
|
Sign up to set email alerts
|

The role of O6-alkylguanine-DNA alkyltransferase in protecting Rat4 cells against the mutagenic effects of O6-substituted guanine residues incorporated in codon 12 of the H-ras gene

Abstract: The role of rat O6-alkylguanine-DNA alkyltransferase (AGT) in modulating mutagenesis by O6-substituted guanines in the rat H-ras gene was examined. Rat4 cells were transfected with vectors carrying O6-methyl-, O6-ethyl- or O6-benzylguanine residues in place of the normal guanines at either the first, second, or both the first and second positions in codon 12 (GGA) of the H-ras coding sequence. The percentage of transformed colonies was determined for cells grown in normal medium or in medium containing O6-benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…The primary mechanism for the aetiology of these G:C→A:T transitions is likely deamination of 5-meC, leading to formation of thymine, since a significant number of mutations were detected at 5Ј-CpG-3Ј sites. The recovery of this mutation at non-CpG sites after NDBzA treatment may be caused by O 6 -benzylG, which also produce G→A transitions (35,36). In fact, a significant number of G:C→A:T transitions (10/18 and 5/12 respectively) were detected at 5Ј-GG-3Ј sites, a characteristic not seen in the spontaneous spectrum (18,30).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The primary mechanism for the aetiology of these G:C→A:T transitions is likely deamination of 5-meC, leading to formation of thymine, since a significant number of mutations were detected at 5Ј-CpG-3Ј sites. The recovery of this mutation at non-CpG sites after NDBzA treatment may be caused by O 6 -benzylG, which also produce G→A transitions (35,36). In fact, a significant number of G:C→A:T transitions (10/18 and 5/12 respectively) were detected at 5Ј-GG-3Ј sites, a characteristic not seen in the spontaneous spectrum (18,30).…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that O 6 -benzylG may exert its mutagenic potential through semi-targeted as well as targeted pathways (35). O 6 -BenzylG may induce transitions and/or transversions depending on the surrounding sequence content (35,36). When incorporated at the second guanine position in a 5Ј-GGA-3Ј sequence (H-ras codon 12), O 6 -benzylG induced G→A, G→T and G→C mutations, but induced exclusively G→A mutations when 2242 incorporated at the first guanine position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, O 6 -chloroethylguanine undergoes a spontaneous rearrangement to produce the highly lethal G-C ethane cross-link which cannot be repaired by AGT [11]. Furthermore, the initial lesion generated by 90CE is likely to be a poorer substrate for AGT than the O 6 -methylguanine lesion [30], which has an in vivo t 1/2 in rat liver of 47 min [26]. Thus, for a cell to survive, the AGT level must be large enough to produce a repair rate that clears the G-C ethane cross-link precursor lesions before their transition to a lethal number of cross-links (<10).…”
Section: Discussionmentioning
confidence: 99%
“…Aspects of the mutagenicity and repair of these types of modified bases have been studied previously in mammalian cells using the site-specific mutagenesis approach (1)(2)(3)(4)(5)(6)(7)(8)(9). We have used this approach here to examine mutagenesis and repair of O 6 -methyl (m 6 G)-, O 6 -ethyl (e 6 G)-, and O 6 -benzylguanine (b 6 G), as well O 4 -methylthymine (m 4 T) in human cells.…”
Section: Introductionmentioning
confidence: 99%